(untitled) (Global Journal of Human-Social Science, 2024)
Literary texts are a rich source of linguistic input that can assist learners practice speaking listening reading and writing in addition to illuminating grammar rules and introducing new vocabulary Additionally it has been discovered that literary texts can engage students with various learning styles and offer chances for multisensory classroom experiences Furthermore this paper intends to highlight the use of literature as a popular method for teaching both basic language skills and language areas in our times Reasons for using literary texts in foreign language classroom as well as the main criteria for choosing appropriate literary texts in foreign language classes are stressed to familiarize the reader with the underlying motivations and standards for language teachers when using and selecting literary texts Also the relationship between literature and the teaching of language skills the advantages of various literary genres for language learning and the difficulties faced by language teachers while teaching English through literature are also taken into consideration